Losing a Little Part of Yourself: Families' Experiences With Foreclosure. (September 2019) - Collins, Cyleste C.; Berg, Kristen A.
While quantitative studies have described foreclosure's correlates, and qualitative work has shed light on homeowners' experiences in general, research has not focused specifically on how families with children younger than 18 years experience foreclosure. This study was an exploratory qualitative examination of families' experiences with home foreclosure, focusing especially on the meaning(s) the foreclosure had for them. In-depth interviews were conducted with 29 adult homeowners living with children younger than 18 years during their foreclosures. The analysis revealed key themes of foreclosure threatening personal and social identity, family relationships and routines, and emotional attachment and experiences of loss. Adults tended to blame themselves for the foreclosures as opposed to seeing structural forces as responsible for their predicaments. The findings help illuminate some of the potential mechanisms underlying the negative impact of foreclosure. Understanding families' experiences is critical to formulating services and policies to help affected families regain stability.